2019
DOI: 10.21315/jcdc2019.24.2.2
|View full text |Cite
|
Sign up to set email alerts
|

Building Information Modelling Plan of Work for Managing Construction Projects in Egypt

Abstract: The Royal Institute of British Architects (RIBA) Plan of Work (PoW) together with Building Information Modelling (BIM) guidance documents, developed in the UK, are commonly used in Egypt and the Middle East. However, efforts from academics publishing articles about the experiences of the adoption of such BIM standards in Egypt have been very limited. This research investigates the use of a BIM-RIBA PoW in the construction industry in Egypt. The research aim was achieved through literature review and collecting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…They can be combined with BIM levels as shown in Table 3 with a detailed clarifying for BIM stages which illustrated in Table 4 [13] and as shown in the successive tables from Table 5 to 12 according to RIBA actions and outcomes for each stage which all referred to Ref. [12], [14].…”
Section: Bim and Riba Digital Plan Of Workmentioning
confidence: 99%
“…They can be combined with BIM levels as shown in Table 3 with a detailed clarifying for BIM stages which illustrated in Table 4 [13] and as shown in the successive tables from Table 5 to 12 according to RIBA actions and outcomes for each stage which all referred to Ref. [12], [14].…”
Section: Bim and Riba Digital Plan Of Workmentioning
confidence: 99%
“…In Egypt, Amin and Abanda (2019) provided evidence for the application of BIM in the design and construction of the Mall of Egypt project. A strengths-weaknesses-opportunities-threats (SWOT) analysis was conducted, which identified the excitement of the project participants to learn and use BIM for the project.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In Africa, Amin and Abanda (2019) investigated the BIM state in Egypt and concluded that significant contractors and engineering firms have already made a move to implement BIM. The study by Ezeokoli et al (2016) claimed that there are BIM users and a high level of BIM awareness among construction professionals in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…This step represented a critical obstacle to the authors. The reasons are quite understandable because of the lack of an official record from a reputable organization in Egypt that includes the contacting addresses of BIM practitioners and the limitation in finding engineers with convenient experiences in the domains of BIM [57]. Facing this challenge, the first author has depended on his personal network and online social account of Facebook for finding BIM-related experts.…”
Section: Dematel Questionnaire-based Surveymentioning
confidence: 99%